1992
DOI: 10.1002/ajmg.1320430158
|View full text |Cite
|
Sign up to set email alerts
|

XLMR genes: Update 1992

Abstract: Up to now, we have identified 77 X-linked conditions in which mental retardation is the primary or a major component manifestation. These conditions were subdivided into 2 categories, designated respectively "X-linked mental retardation syndromes" and "Non-specific X-linked mental retardation". Forty genes have been regionally mapped onto the X chromosome. However, in several instances the data were derived from a single family and most lod scores were less than 3.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Many of the XLMR syndromes are associated with abnormalities of the mid-face and eyes [Neri et al, 19921 but none match the phenotype of these males. Stoll et al [19911 reported a family with XLMR and short stature, frontal bossing, depressed nasal bridge with broad tip, and malar hypoplasia in affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the XLMR syndromes are associated with abnormalities of the mid-face and eyes [Neri et al, 19921 but none match the phenotype of these males. Stoll et al [19911 reported a family with XLMR and short stature, frontal bossing, depressed nasal bridge with broad tip, and malar hypoplasia in affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we mapped the disease locus in a Spanish family segregating for one form of nonspecific X-linked mental retardation in Xp22.2-p22.3. Three other MRX loci have been assigned so far to the same chromosomal region, or to a broader region spanning in part Xp22.2-22.3 by linkage studies [see Neri et al, 1992;Kozak et al, 19931. MRX2 shows close linkage to DXS85 [Arveiler et al, 19881. Patients in that family present with a characteristic syndrome of macrocephaly, square face, macroorchidism, and short stature, different from the clinical findings in the Spanish family.…”
Section: Discussionmentioning
confidence: 99%
“…Through studies beginning in the late 1980s, the number of regionally mapped XLMR syndromes and nonsyndromic XLMR families grew steadily (Glass, 1991;Neri et al, 1991Neri et al, , 1992Neri et al, , 1994Lubs et al, 1996Lubs et al, , 1999Chiurazzi et al, 2001). Diagnoses became more specific as genocopies and phenocopies could be, at least to some degree, eliminated.…”
Section: Molecular Contributionsmentioning
confidence: 99%